Strengthening Ethical Responsibility in the Prosecutor's Office: A Comparative Study of Positive Law and Islamic Legal Principles - Sugiarto, Windhu; Suparto Wijoyo; Mitra Uktutias, Sendy Ayu; Julian, Antoni (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
This study explores how ethical responsibility forms the foundation of Organizational Citizenship Behavior (OCB) within law enforcement institutions, using the Prosecutor's Office as a case study. Employing a qualitative approach, it integrates normative and sociological analyses through the dual perspectives of positive law and Islamic ethical principles. The findings indicate that ethical responsibility encompassing integrity, honesty, and a commitment to justice is essential in motivating prosecutors to go beyond formal obligations by engaging in OCB practices such as loyalty, collegial support, and personal initiative. From the standpoint of positive law, OCB enhances institutional effectiveness, while from the perspective of Islamic law, it reflects work ethics rooted in maqāṣid al-sharī‘ah, particularly in promoting justice and public welfare. The study concludes that reinforcing ethical values grounded in both positive law and Islamic teachings can improve professionalism and accountability within the Prosecutor’s Office, contributing to broader legal bureaucratic reform in Indonesia. The academic contribution of this research lies in its integration of universal ethical values and Sharia principles into the study of organizational behavior in the legal sector—an area traditionally dominated by administrative and legalistic paradigms. As such, the study offers a more contextualized and transdisciplinary ethical-normative approach to legal reform.